2001
DOI: 10.3141/1780-04
|View full text |Cite
|
Sign up to set email alerts
|

Travel Impacts of Mixed Land Use Neighborhoods in Seattle, Washington

Abstract: In response to suburban transportation problems, developers and planners have suggested that mixing land uses can reduce automobile dependency by making more goods and services available within walking, biking, and short driving distances. This view has resulted in a neotraditional planning movement that promotes neighborhoods designed with traditional characteristics including a mix of land uses. However, few studies have empirically explored the transportation implications for these neighborhoods. This issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 6 publications
0
29
1
Order By: Relevance
“…Figure 6a reveals that land-use mix has a strong positive effect on online car-hailing travel, especially in the southeast region, that is, there is more online car-hailing travel in the areas with a high degree of land-use mix. However, this finding is inconsistent with previous studies investigated by Cervero (1996), Mccormack et al (2001), Munishi (2016), Yin Chaoying (2018), Xie Weihan (2018) and others, who recognized land-use mix as an effective strategy to reduce car travel by incorporating sufficient living facilities (e.g., presence of offices, residences, retail, and other uses) [7,19,[34][35][36]. Chunxi Road, a famous commercial zone in Chengdu, has a high level of land-use mix with numerous shopping stores, recreational facilities, office buildings, residential buildings, a hospital, etc.…”
Section: Model Results and Discussioncontrasting
confidence: 99%
“…Figure 6a reveals that land-use mix has a strong positive effect on online car-hailing travel, especially in the southeast region, that is, there is more online car-hailing travel in the areas with a high degree of land-use mix. However, this finding is inconsistent with previous studies investigated by Cervero (1996), Mccormack et al (2001), Munishi (2016), Yin Chaoying (2018), Xie Weihan (2018) and others, who recognized land-use mix as an effective strategy to reduce car travel by incorporating sufficient living facilities (e.g., presence of offices, residences, retail, and other uses) [7,19,[34][35][36]. Chunxi Road, a famous commercial zone in Chengdu, has a high level of land-use mix with numerous shopping stores, recreational facilities, office buildings, residential buildings, a hospital, etc.…”
Section: Model Results and Discussioncontrasting
confidence: 99%
“…Many studies have suggested that improving the quality of life in urban neighborhoods, for example, by promoting mixed land-use, establishing walking communities, developing a sense of place, and encouraging attractive communities, tends to create a harmoniously built environment for citizens [2,3]. Cho and Rodríguez [11] analyzed the relationship between the location of the neighborhood, its built environment, and walking for various purposes.…”
Section: Livable Renovation Of Existing Neighborhoodsmentioning
confidence: 99%
“…Feedback from the respondents suggests that the terms 'compact' and 'dense' need to be clearly defined. Three participants (2,3,7) affirmed that the 'compact' city is the only feasible form for a sustainable city.…”
Section: Perception 3: Inconsistency In the Definition Of 'Density'mentioning
confidence: 99%
See 1 more Smart Citation
“…Ewing et al [21] and Hong et al [25] found that road network density is also negatively correlated with household car ownership; however, the effect of design on car ownership is weaker than the effects of density and diversity [26]. Destination accessibility is a built environment index at the regional level and generally includes distance to central business district (CBD) and job accessibility [27,28]. Empirical studies have shown that vehicle ownership decreases with distance to CBD [20,29].…”
Section: Literature Reviewmentioning
confidence: 99%